Population proteomics as a novel tool for breed characterization: practical considerations - Zanetti, Enrico; Cassandro, Martino (Acta Agraria Kaposváriensis, 2010)
The aim of this study was to describe the pros and cons of a population proteomic approach aiming to characterize local chicken breeds. The experiment involved a total of 29 males of Pépoi, Padovana, and Ermellinata di Rovigo Italian local chicken breeds. Sarcoplasmic protein fractions of breast muscle were analysed by two-dimensional electrophoresis. Image analysis followed by statistical analysis enabled to differentiate groups of individuals on the basis of similarities of protein expression. Individuals well clustered into groups corresponding to the breed of origin. The Significance Analysis of Microarray analysis enabled identification of the most relevant spots regarding breed differentiation; 10 of these were identified by Mass Spectrometry, revealing preliminary evidences on the mechanisms of the breed differentiation process. The approach succeed in differentiating the individuals in groups corresponding to the different breeds, unfolding the relations among breeds and single individuals, analyzing and measuring the genetic variation at encoding loci. Results evidenced the ability to proteomic analyses to identify and to characterize chicken breeds.